COMPARISON OF RAT LIVER MITOCHONDRIAL AND MICROSOMAL MEMBRANE PROTEINS - Schnaitman, Carl A. (1969)
An improved method is described for dissolving membrane proteins and for resolving them by polyacrylamide gel electrophoresis. With this procedure, the inner mitochondrial membrane has been found to contain 23 different protein species and the outer membrane 12. Only one protein species appears to be common to the two membranes. Smooth and rough microsomal membranes contain 15 different proteins. The approximate molecular weight and relative amount of each protein species have been extrapolated from the gel patterns. The outer mitochondrial membrane and the smooth microsomal membrane contain at least three protein species that appear to be identical, suggesting that they possess a common origin.